UPAYA MENURUNKAN HIPERTERMI DENGAN PEMBERIAN KOMPRES KOMBINASI TEKNIK BLOK DAN SEKA (TEPID WATER SPONGE) PADA PASIEN ANAK MENINGITIS DI BANGSAL PADMANABA BARAT RSUP DR SARDJITO - Rahmatika, Shallinda; Herawati, Wiwik; Margaretha, Sumarti Endah Purnamaningsih Maria (Jurnal Kesehatan Karya Husada, 2022)
Background : Meningitis is a condition where the maninges membrane or the thin membrane that surrounds the brain and spinal cord becomes infected which causes inflammation, this is caused by bacteria and viruses. The actual data obtained from the West Padmanaba room register of meningitis cases in the period January-April 2022 there were 28 children. Hyperthermia is one of the common symptoms that often arise due to this inflammation. Hyperthermia is a condition where body temperature is above the normal limit or >37.5°C. Hyperthermia can be overcome by pharmacological and non-pharmacological. One of the non-pharmacological interventions that can be done is using a tepid water sponge compress, which is a compress by combining block and wiping techniques. Objective : To describe the application of a compressive combination of block and wiping techniques (tepid water sponge) to reduce hyperthermia in pediatric meningitis patients in the West Padmanaba ward of Dr Sardjito Hospital. Methods: This study uses a descriptive method in the form of a case study. Results : The action taken on one respondent for 3 times showed the average body temperature before the TWS action was 38.0°C and the average body temperature after the TWS action was 37 ,2°C. Conclusion : Combination of block compresses and wiping techniques (tepid water sponge) can reduce hyperthermia in pediatric meningitis patients in the West Padmanaba ward of Dr Sardjito Hospital with an average decrease in body temperature of 0.8°C.